Impact of COVID-19 pandemic on injury prevalence and pattern in the Washington, DC Metropolitan Region: a multicenter study by the American College of Surgeons Committee on Trauma, Washington, DC. Issue 1 (19th January 2021) - Chodos, Marc; Sarani, Babak; Sparks, Andrew; Bruns, Brandon; Gupta, Shailvi; Michetti, Christopher P; Crane, Joshua; Hall, Erin; Trankiem, Christine T; Abouassaly, Chadi; Haut, Elliott R; Etchill, Eric; et al.
Abstract : Background: The COVID-19 pandemic has had far-reaching effects on healthcare systems and society with resultant impact on trauma systems worldwide. This study evaluates the impact the pandemic has had in the Washington, DC Metropolitan Region as compared with similar months in 2019. Design: A retrospective multicenter study of all adult trauma centers in the Washington, DC region was conducted using trauma registry data between January 1, 2019 and May 31, 2020. March 1, 2020 through May 31, 2020 was defined as COVID-19, and January 1, 2019 through February 28, 2020 was defined as pre-COVID-19. Variables examined include number of trauma contacts, trauma admissions, mechanism of injury, Injury Severity Score, trauma center location (urban vs. suburban), and patient demographics. Results: There was a 22.4% decrease in the overall incidence of trauma during COVID-19 compared with a 3.4% increase in trauma during pre-COVID-19. Blunt mechanism of injury decreased significantly during COVID-19 (77.4% vs. 84.9%, p<0.001). There was no change in the specific mechanisms of fall from standing, blunt assault, and motor vehicle crash. The proportion of trauma evaluations for penetrating trauma increased significantly during COVID-19 (22.6% vs. 15.1%, p<0.001). Firearm-related and stabbing injury mechanisms both increased significantly during COVID-19 (11.8% vs. 6.8%, p<0.001; 9.2%, 6.9%, p=0.002, respectively). Conclusions and relevance: The overall incidence of trauma has decreased since the arrival of COVID-19. However, there has been a significant rise in penetrating trauma. Preparation for future pandemic response should include planning for an increase in trauma center resource utilization from penetrating trauma. Level of evidence: Epidemiological, level III.